Review of antimicrobial use and considerations in the elderly population - Giarratano A (Dove Medical Press, 2018)
Angela Giarratano,1 Samantha EL Green,1 David P Nicolau2 1Department of Pharmacy, Hartford Hospital, Hartford, CT, USA; 2Center for Anti-Infective Research and Development, Hartford Hospital, Hartford, CT, USA Abstract: Pharmacologic management of infections in elderly patients presents multiple challenges to health care professionals due to variable pharmacokinetics, pharmacodynamics, and immune function. Age is a well-established risk factor for infection, but furthermore is a risk factor for prolonged length of hospital stay, increased incidence of complications, and significant and sustained decline in baseline functional status. In 2014, 46.2 million Americans were aged ≥65 years, accounting for 14.5% of the total population. By 2033, for the first time, the population of persons aged ≥65 years is projected to outnumber the people <18 years of age. According to the National Ambulatory Medical Care Survey and the National Hospital Ambulatory Medical Care Survey, 154 million prescriptions for antimicrobials were estimated to have been written in doctors’ offices and emergency departments during a 1-year time period. In 2014, 266.1 million courses of antimicrobials were dispensed to outpatients by US community pharmacies. A study that evaluated 2007–2009 Medicare Part D data found that patients aged ≥65 years used more antimicrobials, at 1.10 per person per year, compared to 0.88 antimicrobials used per person per year in patients aged 0–64 years. With the abundance of antimicrobial prescriptions and the current growth in the number and proportion of older adults in the US, it is essential that health care providers understand appropriate antimicrobial pharmacotherapy in the elderly patient. This review focuses on the use and implications of antimicrobial agents in the elderly population. Keywords: infection, age, drug resistance, bacterial